Step up and Speak Out: Sexual Violence - Priyadharishini J, Joy; Shan Mathew, Lishma (Indian Journal of Nursing Sciences, 2024)
Sexual violence occurs all over the world irrespective of the status, age, or even gender. It leaves a long-lasting physical and emotional trauma to the victims. Sexual violence has been a neglected area of research in most parts of the world. It is vital to develop interventions for resource-poor settings and rigorously to evaluate programs in both industrialized and developing countries. Sexual violence is a major problem faced by women and girls in India. Violence against women in India is actually more present than it may appear at first glance, as many expressions of violence are not considered crimes, or may otherwise go unreported or undocumented due to certain Indian cultural values and beliefs. Violence against women is a social, economic, developmental, legal, educational, human rights, and health (physical and mental) issue. It is already a challenge for survivors to obtain justice in the Indian legal system, and those from the country’s marginalized communities face even more major barriers. Ultimately, the strong commitment and involvement of governments and civil society, along with a coordinated response across a range of sectors, are required to end sexual violence. As nations plan strategies to contain emerging diseases, it also has to consider this immoral behavior and make measures for people to live free from the fear of harassment